(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
The phenological phases of the quince varieties “Samarkandskaya krupnoplodnaya” (st), “Aromatnaya”, “Izobelnaya”, “Mushk behi”, “Savkhoznaya”, “Krimskaya aromatnaya”, “Otlichnitsa” the introduced varieties “Anjerskaya”, “Grushavidnaya”, “Zakatolskaya”, “Konservnaya”, “Micha urojaynaya”, “Nagibrin”, “Tursh Bukharskaya” and the folk selection varieties “Non behi”, “Nordon” were studied. As a result of the study, it was found that the period from budding to the end of the growing season of trees lasted from 200 to 225 days.